2012 IEEE 11th International Conference on Cognitive Informatics and Cognitive Computing 2012
DOI: 10.1109/icci-cc.2012.6311155
|View full text |Cite
|
Sign up to set email alerts
|

Vocal interaction in collocated cooperative design

Abstract: Using vocal interfaces in complex applications leads to more intuitive interactions. At the University of Technology of Compiègne, we have built a collaborative environment from a large graphics table, interactive board and peripheral devices for supporting preliminary cooperative design. The environment support unique multimodal interaction through intelligent personal assistant agents and this paper details the architecture and implementation of their vocal interfaces, as well as the multiagent middleware, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Moreover it has been shown that natural language dialogues in a professional context are not very difficult to implement (Barthès [26], Fuckner et al [27]). Finally, speech-to-text and text-to-speech programs have made enough progress to be now integrated in such kinds of interfaces (Jones et al [28]).…”
Section: F User Dimensionmentioning
confidence: 99%
“…Moreover it has been shown that natural language dialogues in a professional context are not very difficult to implement (Barthès [26], Fuckner et al [27]). Finally, speech-to-text and text-to-speech programs have made enough progress to be now integrated in such kinds of interfaces (Jones et al [28]).…”
Section: F User Dimensionmentioning
confidence: 99%